Range-resolved optical interferometric signal processing - Kissinger, Thomas (Cranfield University, 2015)
The ability to identify the range of an interferometric signal is very useful in interferometry, allowing the suppression of parasitic signal components or permitting several signal sources to be multiplexed. Two novel range-resolved optical interferometric signal processing techniques, employing very different working principles, are theoretically described and experimentally demonstrated in this thesis. The first technique is based on code-division multiplexing (CDM), which is combined with single-sideband signal processing, resulting in a technique that, unlike prior work, only uses a single, regular electro-optic phase modulator to perform both range-based signal identification and interferometric phase evaluation. The second approach uses sinusoidal optical frequency modulation (SFM), induced by injection current modulation of a diode laser, to introduce range-dependent carriers to determine phase signals in interferometers of non-zero optical path difference. Here, a key innovation is the application of a smooth window function, which, when used together with a time-variant demodulation approach, allows optical path lengths of constituent interferometers to be continuously and independently variable, subject to a minimum separation, greatly increasing the practicality of the approach. Both techniques are applied to fibre segment interferometry, where fibre segments that act as long-gauge length interferometric sensors are formed between pairs of partial in-fibre reflectors. Using a regular single-mode laser diode, six fibre segments of length 12.5 cm are multiplexed with a quadrature bandwidth of 43 kHz and a phase noise floor of 0.19 mrad · Hz -0.5 using the SFM technique. In contrast, the 16.5 m spatial resolution achieved with the CDM technique points towards its applicability in medium-to-long range sensing. The SFM technique also allows high linearity, with cyclic errors as low as 1 mrad demonstrated, and with modelling indicating further room for improvement. Additionally, in an industrial measurement, the SFM technique is applied to single-beam, multi-surface vibrometry, allowing simultaneous differential measurements between two vibrating surfaces.